Interpretation of insecticide posters by rice farmers in selected villages in Leyte, Philippines - Cortes, Dennis C. (Annals of Tropical Research, 2016)
Farmers usually get pesticide information from different sources, such as radio, television, print ads, extension technicians, pesticide sales agents, other farmers, and their own experience. This study focused on rice farmers’ interpretation of insecticide use in outdoor print advertisements in selected rice growing provinces in Leyte, Philippines. One hundred farmers were individually presented with six insecticide posters and asked to give their feedback. A focus group discussion was also conducted to obtain more insights into the participants’ assessment of the poster’s ability to grab attention, their understanding of the message, perceived acceptability, and self-involvement. Packaging (insecticide bottle), images that connote power and strength such as boxing gloves, superman and the peso sign, slogan, color, and brand name were found to be attractive elements of the posters. Most respondents understood the message conveyed by nearly all posters. Only a few respondents found something offensive and untrue in the text and slogans used. Overall results of the study proved that insecticide posters were effective in encouraging unnecessary insecticide use. Focus group discussion results indicated that farmers had knowledge gaps and misconceptions of the posters’ message. For instance, they misconstrued that the posters encouraged them to use more insecticides when that recommendation was not in the posters. It appears that pesticide use has been well entrenched in the minds of farmers that a poster appears to be a trigger for insecticide use.